Employee Readiness in the AI Era: The Role of Digital Literacy, Adaptive Competence, and Training with Organizational Support as a Moderating Variable - Jagad, Daniel Jaya (Electronic Journal of Education, Social Economics and Technology, 2025)
The rapid advancement of artificial intelligence (AI) and digital transformation has redefined the demands of the modern workplace, requiring employees to develop the readiness to adapt to continuous technological change. This study aims to examine the influence of digital literacy, adaptive competence, and training on employee readiness, with organizational support acting as a moderating variable. Using a quantitative approach and explanatory research design, data were collected through a structured questionnaire distributed to 96 employees of a technology-integrated organization in Makassar. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results reveal that training and organizational support have a significant positive effect on employee readiness. Furthermore, the interaction between training and organizational support strengthens this relationship, highlighting the importance of strategic synergy between individual capacity development and institutional support. However, digital literacy and adaptive competence did not show significant direct effects on employee readiness. Notably, the interaction between adaptive competence and organizational support showed a negative moderating effect, while the interaction between digital literacy and organizational support was statistically insignificant. These findings suggest that employee readiness in the AI era is best supported through future-oriented training programs and enabling organizational environments. Organizations are advised to align digital literacy development with practical needs, foster adaptive behavior without excessive control, and implement structured yet flexible support systems. A holistic approach integrating technical training, psychological preparedness, and contextual organizational support is key to building resilient and agile workforces in the face of technological disruption.